Hubungan Digital Stress terhadap Social Media Addiction pada Remaja Akhir sebagai Pengguna Aktif Media Sosial - Novita, Tiara; Utami, Rahayu Hardianti (Lembaga Yasin AlSys, 2024)
This study aims to determine the relationship between digital stress and social media addiction in late adolescents as active users of social media. The research method used is descriptive quantitative with purposive sampling technique. The sample consisted of 300 respondents aged 18-24 years who actively use social media. Data collection used digital stress scale based on aspects of Hall (2021) and Bergen Social Media Addiction Scale (BSMAS) based on aspects of Griffiths (2005). Data analysis used product moment correlation test. The results showed that there was a significant positive relationship between digital stress and social media addiction with a Pearson correlation coefficient of 0.393. The subject's digital stress level was in the moderate category (54%), while 81.7% of subjects experienced social media addiction. The results of this study indicate that digital stress has a relationship with social media addiction in late adolescents who are active users of social media.